Identification of Sub-Fault Zone Using Magnetotelluric Inversion (Case Study: Ketaun Fault, Lemeu Village, Lebong Regency) - Rahmawati, Nurul Ilmi; Farid, Muchammad; Hadi, Arif Ismul; Al Ansory, Andre Rahmat (Departemen Geofisika, FMIPA - Universitas Hasanuddin, Makassar, 2024)
Lemeu Village, Lebong Regency, borders the Bukit Barisan Mountain range and is crossed by the Ketaun Fault, which causes a high level of seismic activity, so it is necessary to conduct research on the potential existence of the Ketaun sub-fault as one of the efforts to mitigate natural disasters such as earthquakes. The Magnetotelluric method utilises the earth's natural electromagnetic field, which is used to determine the distribution of resistivity in the subsurface using the ADU-07e Magnetotelluric tool with two horizontal electrical sensors (Ex, Ey) and three horizontal (Hx, Hy) and vertical (Hz) magnetic sensors and uses seven research points with an interval of 1 km. Data processing uses MAPROS software to convert data from the time domain to the frequency domain and ZONDMT2D to obtain subsurface resistivity values. The results obtained from this study are 2D magnetotelluric cross sections showing a zone with low resistivity values between research points P4 and P5 which is thought to be a new fault zone with resistivity values ranging from 1.3 – 6.1 Ωm from a depth of 2.5 km to a depth of 10 km. The zone is assumed to be a new fault that is a branch of the Ketaun fault.